2019
DOI: 10.1093/cid/ciz991
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Impact of Implementing OVIVA Criteria on Patients With Bone and Joint Infections in Outpatient Parenteral Antimicrobial Therapy

Abstract: The OVIVA study demonstrated noninferiority for managing bone and joint infections (BJIs) with oral antibiotics. We report that 79.7% of OPAT patients being treated for BJIs at our center would be eligible for oral antibiotics, saving a median (IQR) 19.5 IV-antibiotic days (8.5–37) and GBP 1234 (569–2594) per patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Oral antibiotics may be used when re-evaluating EAT, as the Oral versus Intravenous Antibiotics for Bone and Joint Infection (OVIVA) trial demonstrated that switching to an oral regiment within 7 days after surgery was noninferior to intravenous antibiotic treatment, with significant cost savings [30,31]. Lack of stable venous access is a common difficulty that justifies earlier adaptation of the EAT.…”
Section: Discussionmentioning
confidence: 99%
“…Oral antibiotics may be used when re-evaluating EAT, as the Oral versus Intravenous Antibiotics for Bone and Joint Infection (OVIVA) trial demonstrated that switching to an oral regiment within 7 days after surgery was noninferior to intravenous antibiotic treatment, with significant cost savings [30,31]. Lack of stable venous access is a common difficulty that justifies earlier adaptation of the EAT.…”
Section: Discussionmentioning
confidence: 99%
“…One such study evaluated the economic impact of transition to COpAT in eligible patients with bone and joint infections demonstrated a 19.5 day reduction in IV antimicrobial administration which was associated with £1234 ($1746.48) in cost savings per patient. Notably, in this study, those who transitioned to COpAT did so after a median of 17 days of OPAT, thereby demonstrating the value of ambulatory OPAT to COpAT transition [ 12 •].…”
Section: Regimen Redesign From Opat To Copatmentioning
confidence: 88%
“…A study of pediatric patients comparing economic and patient-related benefits of those receiving COpAT with those receiving OPAT found COpAT was associated with significantly lower direct costs of therapy, less missed school for children, less missed work for caregivers, a higher level of caregiver comfort with the planned regimen, and better caregiver quality of life [ 11 ]. Multiple studies have evaluated the impact of the use of oral antimicrobials or implementation of protocols allowing for the use of oral antibiotics in the treatment of bone and joint infections [ 12 •, 13 ]. One such study evaluated the economic impact of transition to COpAT in eligible patients with bone and joint infections demonstrated a 19.5 day reduction in IV antimicrobial administration which was associated with £1234 ($1746.48) in cost savings per patient.…”
Section: Regimen Redesign From Opat To Copatmentioning
confidence: 99%
“…In this study, two-thirds of patients had PJI and 40% of infections were due to S. aureus . Importantly, studies derived from the OVIVA trial have shown that early outpatient parenteral antimicrobial therapy could be used in 80% of patients [ 13 ] and would decrease length of stay, treatment costs and vascular device-related complications [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%